Penerapan Metode Pembelajaran Kooperatif Tipe Group Investigation untuk Meningkatkan Hasil Belajar Peserta Didik - ririn, ririn; Zuhdi, Rasyid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The ability to improve learning outcomes for students by going through the process to achieve satisfactory results can arouse students' enthusiasm and confidence in understanding the material to improve their learning outcomes. With the existence of new ways to improve student learning outcomes, one of which is using the Group Investigation type cooperative method, it can make students more enthusiastic, creative and there is social value, namely in this cooperative learning, students are also able to work together in small groups, there is positive dependence (mutual need), mutual assistance, and mutual motivation in order to achieve the desired goals and results. Researchers conducted this study to determine whether or not there was an increase in Group Investigation Type Cooperative Learning for Student Learning Outcomes. The data from this study were collected using a learning achievement test. While the analysis uses descriptive analysis. After all the data were analyzed, it was found that the increase in learning outcomes from the beginning reached 65.80 with a learning completeness of 53.27 in cycle I. The results of cycle II on average increased to 75.63 with a learning completeness of 73.61 and in cycle III increased again to 85.47 learning completeness 88.30 It turns out that the results in cycle III have exceeded the proposed criteria according to the research success indicators. This is evidenced from data collection about student learning outcomes included in the good category through 3 cycles. On the basis of the data obtained, the researcher concluded that the application of the Group Investigation Type Cooperative Method was able to improve student learning outcomes.